I'm trying to convert a string like 'a?(b?c:d):e'
to another string 'ifthenelse(a,ifthenelse(b,c,d),e)'
using the lpeg lua parser. I'm slowly learning how to use lpeg but still I can't find a suitable solution to do this with captures. Any ideas?
Here is what I did so far.
local lpeg = require("lpeg")
local S, P, R = lpeg.S, lpeg.P, lpeg.R
local C, Cc, Ct = lpeg.C, lpeg.Cc, lpeg.Ct
local Cf, Cg, Cs = lpeg.Cf, lpeg.Cg, lpeg.Cs
local V = lpeg.V
local thenop = P("?")
local elseop = P(":")
local openpar = P("(")
local closepar = P(")")
local digit = R("09")
local letter = R("az") + R("AZ")
local parser =
P({
"F",
F = V("E") * (thenop * V("E") * elseop * V("E"))^0,
E = (letter + digit)^1 + (openpar * V("F") * closepar)
}) -- * -1 -- Is it needed?
print(lpeg.match(parser,"a?(b?c:d):e"))
print(lpeg.match(parser,"a"))
Here is another solution to the problem given by William Ahern on the lua-list.
local lpeg = require("lpeg")
lpeg.locale(lpeg)
local function tr(a, b, c)
if not b then
return a
else
return string.format("ifthenelse(%s,%s,%s)", a, b, c)
end
end
local var = lpeg.C(lpeg.alpha * (lpeg.alnum^0))
local E, G = lpeg.V"E", lpeg.V"G"
local grammar = lpeg.P{ "E",
E = ((var + G) * (lpeg.P"?" * E * lpeg.P":" * E)^-1) / tr,
G = lpeg.P"(" * E * lpeg.P")",
}
print(lpeg.match(grammar, "a?(b?c:d):e"))